PERSEPSI SISWA TERHADAP LITERASI DIGITAL BERBASIS TIKTOK DALAM MENINGKATKAN MINAT BELAJAR PPKn DI SMP NEGERI 32 MEDAN - Satya Nofryanti N.; Sri Yunita (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The low interest of students in learning the Pancasila and Citizenship Education (PPKn) subject is one of the main challenges faced by SMP Negeri 32 Medan. This is caused by the use of conventional learning methods and the lack of technology integration in the teaching and learning process. Therefore, this study aims to analyze how students perceive TikTok-based digital literacy in increasing interest in learning PPKn and how TikTok-based digital literacy can increase students' interest in learning. The type of research used is descriptive with a qualitative research method. The subjects in this study were students of class VIII-3 at SMP Negeri 32 Medan who were selected using purposive sampling techniques based on the consideration that students in this class have active involvement with TikTok social media but show low interest in learning PPKn. Data collection techniques were carried out through observation, in-depth interviews, and documentation, while data analysis was carried out in three stages, namely data reduction, data presentation, and drawing conclusions. This research is expected to provide benefits both academically and practically. The results of the study showed that the use of TikTok-based digital literacy can increase students' interest in learning PPKn. Students show feelings of joy, interest, more attention when learning, and active involvement in the learning process. With an approach that suits the interests and characteristics of the digital generation, TikTok can be an innovative, interactive learning medium, while strengthening students' digital literacy in the 4.0 era.